Environmental Features Influence Walking Speed: The Effect of Urban Greenery - Marek Franěk; Lukáš Režný (Land, 2021)
The study investigated the rarely addressed topic of how visual environmental features can influence walking speed. Young adult participants were asked to walk on a route that leads through areas composed of urban parks and areas with a built environment with a large amount of greenery. Their walking speed was measured in selected sections. The participants walked with a small video camera, and their walk was recorded. The temporal information was derived from the video recordings. Subsequently, the participants evaluated the environmental features of the route by specific spatio-cognitive dimensions of environmental preference. The results show that walking speed in specific sections of the walking route systematically differed and reflected the environmental features. The walking speed was lower in sections with high natural characteristics and a high environmental preference. Noise here was perceived as less annoying than in sections with lower natural characteristics. The results are explained in terms of approach avoidance behavior. The findings are in accordance with environmental preference research that documents various benefits of walking in the natural environment.